Karakteristik Media Pembelajaran Matematika di Sekolah Dasar - Elvi Mailani; Nur Rarastika; Nazwa Audina br. Manurung; May Ardiani Rajagukguk; Sofia Utami Siregar (GLOBAL SCIENTS PUBLISHER, 2025)
Mathematics learning at the elementary school level plays an important role in developing students' logical, critical, and systematic thinking skills. Effective learning media should be able to simplify abstract concepts into more concrete forms, expand material presentation, and overcome space, time, and sensory limitations during the learning process. This study aims to identify and analyze the characteristics of mathematics learning media used in elementary schools and evaluate its relevance to students' learning needs. A qualitative descriptive approach was employed through review of relevant literature sources. The results indicate that appropriate media can increase students' active engagement in mathematics learning and facilitate understanding of abstract concepts. It is hoped that these findings can serve as a reference for developing more innovative and student-centered learning media.